Assessing steel and composite highway structures: background to new UK design standards. Issue 3 (19th September 2021) - Robinson, Peter; Sandberg, Jessica; Hendy, Chris; Gallagher, Jim
Abstract : The UK's design documents for assessment of steel and composite highway bridges and structures have been updated in line with Highways England's overall plan for modernising the Design Manual for Roads and Bridges . This paper describes the key changes that have been made to the document and their impact on users, providing reassurance that, despite the new format, the methods and requirements are largely unchanged, or changed to facilitate future assessments by allowing more general approaches to be adopted. For steel bridges the key changes are described that affect robustness assessment, notch toughness, bearing stiffeners, cross-girders, stiffened panel buckling and inspection criteria for existing welds. For composite bridges, the changes relate mainly to the serviceability limit state verifications, to fatigue and to the shear connection, as well as the general improvements to remove outdated content and simplify the document. The changes for both documents include greater references to the Eurocodes in general, which will facilitate an easier transition to Eurocode assessment standards when these are published in the future.